2018
DOI: 10.1002/brb3.955
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cortical lesions and cognitive impairment in multiple sclerosis

Abstract: ObjectivesGray matter (GM) damage is well known as a fundamental aspect of multiple sclerosis (MS). Above all, cortical lesions (CLs) burden, detectable at MRI with double inversion recovery (DIR) sequences, has been demonstrated to correlate with cognitive impairment (CI). The aim of this study was to investigate the role of CLs number in predicting CI in a cohort of patients with MS in a clinical practice setting.Materials and methodsThirty consecutive patients with MS presenting CLs (CL+) at high‐field (3.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
4
14
2
Order By: Relevance
“…Only few studies have investigated the contribution of CL load assessed at 7T to clinical MS disability. Even if derived from relatively small cohorts (up to 36 patients), the data obtained from cross-sectional studies 27,28 confirm the findings observed at lower field strength [29][30][31][32][33] regarding the relationship between high CL load and higher Expanded Disability Status Scale (EDSS) scores and cognitive impairment. Furthermore, the same studies have shown that CL subtypes might have a different clinical relevance.…”
Section: -Cortical Lesion Evolution and Relation To Clinical Outcomesupporting
confidence: 54%
“…Only few studies have investigated the contribution of CL load assessed at 7T to clinical MS disability. Even if derived from relatively small cohorts (up to 36 patients), the data obtained from cross-sectional studies 27,28 confirm the findings observed at lower field strength [29][30][31][32][33] regarding the relationship between high CL load and higher Expanded Disability Status Scale (EDSS) scores and cognitive impairment. Furthermore, the same studies have shown that CL subtypes might have a different clinical relevance.…”
Section: -Cortical Lesion Evolution and Relation To Clinical Outcomesupporting
confidence: 54%
“…Burden of lesion is often measured by grey matter damage, which is measured either as cortical lesion (CL) or as cortical atrophy. Total CLs number was also found to predict cognitive impairment in verbal memory, information processing speed, working memory and attention in comparing between 30 MS patients with CL and 30 MS patients without CL (Curti et al 2018).…”
Section: Methodsmentioning
confidence: 90%
“…According to Curti et al (2018), frontal lobe is the most affected region by CL, followed by temporal and parietal lobe. On the other hand, according to Papadopoulou and colleagues (2013), even though CL volume was correlated with information processing speed, working memory and attention, white matter damage significantly predicted cognitive impairment instead.…”
Section: Methodsmentioning
confidence: 99%
“…Damage of the temporal cortices has been associated with cognitive impairment, 30 whereas involvement of the lateral orbitofrontal cortex and the inferior parietal lobule has been correlated with associative dysfunction, ideomotor apraxia, sensory agnosia and visual disturbances, 31 which interfere in the patients’ clinical performance. Indeed, lateral orbitofrontal cortices and the left inferior parietal lobule showed also associations with concomitantly worse EDSS scores, mirroring the sensitivity of the EDSS for the detection of sensorimotor 32 and visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…28 In MS patients, a more severe atrophy of the left precuneus (observed especially in RRMS patients) was associated with a higher LV, reinforcing the notion 4,5,12 that overall CTh reduction in the RR disease phases might be (at least partially) originated by Wallerian retrograde degeneration. 29 Damage of the temporal cortices has been associated with cognitive impairment, 30 whereas involvement of the lateral orbitofrontal cortex and the inferior parietal lobule has been correlated with associative dysfunction, ideomotor apraxia, sensory agnosia and visual disturbances, 31 which interfere in the patients' clinical performance. Indeed, lateral orbitofrontal cortices and the left inferior parietal lobule showed also associations with concomitantly worse EDSS scores, mirroring the sensitivity of the EDSS for the detection of sensorimotor 32 and visual impairment.…”
Section: Discussionmentioning
confidence: 99%